Mode-locked generation in thulium-doped fiber linear cavity laser - Latiff, Anas Abdul; Shamsudin, Hanafiah; Aziz, Nur Suhaili Abd; Hashim, Abdul Manaf; Irawati, Ninik; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2016)
A simple all fiber passive mode-locked thulium-doped fiber (TDF) linear cavity laser operating at 1901.6 nm with an incorporation of homemade graphene oxide paper (GOP) based saturable absorber is proposed and practically demonstrated. The TDF linear cavity laser generates mode-locking pulse at a threshold pump power of 540 mW. By varying the pump power from the threshold power to 1052 mW, pulse repetition rates remain constant at 82.4 MHz. At the maximum pump power of 1052 mW, the pulse width is estimated as 12.66 ps, whereas the pulse energy is calculated as 83.1 pJ.